The Influence of Risk Management and Social Sustainability on Supply Chain Integration and Performance in Multinational Companies in the Era of Globalization - Safuan, Safuan; Subagyo, Imam; Cornellius, Josephin; Muallifah, Siti; Yusnaini, Yusnaini (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2024)
This research explores the influence of supply chain risk management and social sustainability on supply chain integration and performance in multinational companies in the era of globalization. The study aims to understand how risk management practices and social sustainability can affect various aspects of supply chain integration, including supplier integration, customer integration, and internal integration, as well as their impact on overall supply chain performance. Using a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from 301 respondents working in various multinational companies in Indonesia. The results of the study indicate that supply chain risk management has a significant positive influence on supplier integration, customer integration, and internal integration. Additionally, social sustainability is shown to strengthen the relationship between risk management and both customer integration and internal integration, although it does not strengthen the relationship between risk management and supplier integration. Internal integration is found to have a significant positive impact on supplier integration but not on customer integration. Furthermore, supplier integration and internal integration each have a positive impact on supply chain performance, whereas customer integration does not show a significant impact. This research also highlights the importance of social sustainability in strengthening the relationship between risk management and supply chain integration, as well as its implications for corporate strategies in enhancing supply chain performance amid the challenges of globalization. This study makes an important contribution to the supply chain management literature by emphasizing the strategic role of risk management and social sustainability in strengthening supply chain integration and improving the supply chain performance of multinational companies. The practical implication of this research is that companies need to effectively integrate risk management with social sustainability practices to achieve optimal supply chain performance.